Involvement of phospholipases C and D in early response to SAR and ISR inducers in Brassica napus plants - Profotová, B; Burketová, L; Novotná, Z; Martinec, J; Valentová, O (Plant physiology and biochemistry, 2006)
Phospholipid signaling is an important component in eukaryotic signal transduction pathways. In plants, it plays a key role in growth and development as well as in responses to environmental stresses, including pathogen attack. We investigated the involvement of both phospholipase C (PLC, EC 3.1.4.11) and D (PLD, EC 3.1.4.4) in early responses to the treatment of Brassica napus plants with the chemical inducers of systemic acquired resistance (SAR): salicylic acid (SA), benzothiadiazole (BTH), and with the inducer mediating the induced systemic resistance (ISR) pathway, methyl jasmonate (MeJA). Rapid activation (within 0.5-6 h treatment) of the in vitro activity level was found for phosphatidyl inositol 4,5 bisphosphate (PIP2)-specific PLC (PI-PLC) and three enzymatically different forms of PLD: conventional PLDalpha, PIP2-dependent PLD beta/gamma, and oleate-stimulated PLDdelta. The strongest response was found in case of cytosolic PIP2-dependent PLD beta/gamma after BTH treatment. PLDdelta was identified in B. napus leaves and was very rapidly activated after MeJA treatment with the highest degree of activation compared to the other PLD isoforms. Interestingly, an increase in the amount of protein was observed only for PLDgamma and/or delta after ISR induction, but later than the activation occurred. These results show that phospholipases are involved in very early processes leading to systemic responses in plants and that they are most probably initially first activated on post translational level.
Keywords: listy rostlin; Salicylic Acid; fosfolipasy typu C; Phospholipase D; Oxylipins; regulátory růstu rostlin; oxylipiny; Acetates; Plant Proteins; nemoci rostlin; Time Factors; thiadiazoly; fosfolipasa D; acetáty; Plant Growth Regulators; kyselina salicylová; Plant Leaves; časové faktory; Type C Phospholipases; Cyclopentanes; Plant Diseases; Thiadiazoles; Brassica napus; cyklopentany; rostlinné proteiny